2013
DOI: 10.3389/fphys.2012.00493
|View full text |Cite
|
Sign up to set email alerts
|

Intertwined arbovirus transmission activity: reassessing the transmission cycle paradigm

Abstract: Arboviruses are emerging/reemerging infectious agents worldwide. The factors within this scenario include vector and host population fluctuations, climatic changes, anthropogenic activities that disturb ecosystems, an increase in international flights, human mobility, and genetic mutations that allow spill-over phenomenon. Arboviruses are maintained by biologic transmission among vectors and hosts. Sometimes this biological transmission is specific and includes one vector and host species such as Chikungunya (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…These results suggest the need for additional studies on viral circulation in mosquitoes and hosts. Although equines are important WNV vertebrate hosts, only a limited number of dead or diseased horses have been diagnosed in America (Díaz et al, 2013). These authors suggest that prior exposure to others Flavivirus could modulate the disease in subsequent exposures to WNV, which could be a possible explanation that none of the horses infected with this virus in the present study have developed a clinical response.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These results suggest the need for additional studies on viral circulation in mosquitoes and hosts. Although equines are important WNV vertebrate hosts, only a limited number of dead or diseased horses have been diagnosed in America (Díaz et al, 2013). These authors suggest that prior exposure to others Flavivirus could modulate the disease in subsequent exposures to WNV, which could be a possible explanation that none of the horses infected with this virus in the present study have developed a clinical response.…”
Section: Discussionmentioning
confidence: 62%
“…SLEV is known to cause subclinical infections in horses nevertheless; the first isolation of SLEV from a horse that died due to a neurological disease in Brazil is a significant event. This is the first observation that SLEV can cause disease in horses, which indicates that some aspects of its viral cycle and its ability to cause disease need further studies (Díaz et al, 2013).…”
Section: Resultsmentioning
confidence: 83%
“…increase in abundance with peaks in summer, with are temporal distribution of Culex spp. coinciding with the activity peaks of SLEV in human infection [3,39]. Adult mosquitoes belonging to the species Cx.…”
Section: Discussionmentioning
confidence: 70%
“…The analysis of the dynamic maintenance of these viruses appears to link to a transmission network instead of a transmission cycle [11]. The mechanisms for the maintenance of arboviruses are intrinsically complicated and must be taken into account and incorporated when designing and constructing mathematical models that allow predicting their enzootic/ epidemic activity in a given ecosystem (wild, urban, and agricultural, as well).…”
Section: 5 T T G a A G C At T C C A C At Ta A A G G C C G C C G A Amentioning
confidence: 99%
“…These animals become infected and develop viremia that is sufficient to infect the vectors [9,10]. Different studies have reported evidence of VEEV infection, suggesting that bats (frugivorous, sanguinivorous, and insectivorous) could be host to arboviruses of public health impact in America [11][12][13][14][15]. Clinically, VEEV is indistinguishable from dengue and other arboviral diseases, often humans infected with VEEV symptoms appear within 2-5 days, and range from febrile, or flu-like symptoms, such as malaise, fever, chills, and myalgia, to coma and death are registered in ~1% of cases [3].…”
Section: Introductionmentioning
confidence: 99%